Outcome of Endoscopic Third Ventriculostomy - Adil Aziz Khan, Soban Sarwar Gondal, MuhammadMujahid Sharif, Muhammad Yousaf, Nadeem Akhtar (Journal of Rawalpindi Medical College, 2018)
Background: To study the outcome of endoscopic third ventriculostomy (ETV) Methods: In this observational study an endoscopic third ventriculostomy was applied in patients who suffered from hydrocephaly. The diagnosis of hydrocephalus was determined by physical, neurological and neuro-radiological criteria. Patients with obstructed hydrocephalus whether congenital or acquired, with a dilated 3rd ventricle were included. Linear incision was given 2cm anterior to the coronal suture in mid pupillary line. Right frontal burr hole is made. For ETV, burr hole is placed on a line joining the foramen of monro and inter-peduncular line. Floor of the third ventricle was punctured close to or over the dorsum sellae. Membrane was dilated with balloon. Balloon was inflated and subsequently was taken out from puncture site. It ensured easy visibility of basilar artery and its perforators. Result: Age of patients ranged from 06 months to 24 years, with a mean age of 4 years . Fourteen patients had posterior fossa tumour’s with dilated third ventricle, sixty four patients had aqua ductal stenosis, two patients with CSF ascites as complication of ventriculo-peritoneal shunt, eleven patients had blocked lower end of ventriculoperitoneal shunt. Seven patients had CSF leak. Time taken to complete endoscopic third ventriculostomy was from 20 to 40 min as compared to 1 hour to 1.30 hours, taken in a VP shunt. Patients who had ETV performed had a mean hospital stay of 3 days, where as patients in whom a VP shunt was performed stayed in the ward for an average of 5 to 10 days, depending on how eventful the post op period was. The cost incurred to the VP shunt patient who remained admitted for an average of 5 days was between Rupees 16,000 to 25,000, ascompared to Rs: 2000 for the patient who underwent endoscopic third ventriculostomy. Conclusion: Patients of ETV, with less per operative time, had decreased length of stay. ETV also was less expensive to the patient and he did not have to buy the shunt apparatus with less rehospitalization rates, compared to patients who had undergone shunt.